INVERSI MIKROTREMOR UNTUK PROFILING KECEPATAN GELOMBANG GESER (Vs) DAN MIKOROZONASI KABUPATEN BANDUNG - Andina Zuhaera; Suharno Suharno; Bagus Sapto Mulyatno (Jurnal Geofisika Eksplorasi, 2019)
Bandung Regency is a highland area with a slope between 0 - 8%, 8-15% to above 45%. The district is located at an altitude of 768 m above sea level with the northern region higher than the south. The purpose of this study was to determine the distribution of Vs30 waves and determine the impact of damage due to wave amplification (amplification). To minimize the impact of this earthquake identification can be done including a survey to map soil characteristics in response to earthquake shocks using the seismic Horizontal to Vertical Spectral Ratio (HVSR) method. Based on the results of the study, the distribution of the dominant frequency values, Bandung Regency was identified as having hard and soft rock soil and having solid clay with a thickness of tens of meters. The amplification value in Bandung Regency has a value (0 Ao 6) which can be categorized that Bandung Regency has a small impact on the earthquake. The difference between the results of inversion processing and HVSR is due to the assumption that the layer inversion is heterogeneous and the HVSR layer is homogeneous.